2017
DOI: 10.3390/f8030067
|View full text |Cite
|
Sign up to set email alerts
|

Early REDD+ Implementation: The Journey of an Indigenous Community in Eastern Panama

Abstract: Abstract:Reducing Emissions from Deforestation and Forest Degradation (REDD+) offers developing countries an opportunity to engage in global climate change mitigation through the sale of carbon credits for reforestation, avoided deforestation and forest conservation projects. Funding for REDD+ projects has increased in recent years and REDD+ projects have proliferated, but relatively few studies have, as yet, examined their implementation. Here, we present a synthesis of the challenges and lessons learned whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Here again, hypothetical income from REDD+ might support such initiatives. Assuming a cost of ~US$563 yr -1 to reforest one hectare [ 42 ], approximately 586 ha of land could be restored annually in the watershed if all potential income generated from REDD+ ( i . e .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here again, hypothetical income from REDD+ might support such initiatives. Assuming a cost of ~US$563 yr -1 to reforest one hectare [ 42 ], approximately 586 ha of land could be restored annually in the watershed if all potential income generated from REDD+ ( i . e .…”
Section: Resultsmentioning
confidence: 99%
“…Ostrom [ 43 ], however suggested that bridging organizations that support community initiatives are a key element of the sustainable governance of common resources such as forests. In Ipeti and Piriati, bridging organizations indeed have played a fundamental role in supporting the two communities in REDD+ and PES initiatives [ 42 , 44 ]. External support however is costly.…”
Section: Resultsmentioning
confidence: 99%
“…The extent to which economic returns of the land-use withstand the effects of extreme weather, pests and diseases and price fluctuations Connelly and Shapiro (2006) and Coomes et al (2008) 5 Liquidity Regular cash income, including how easily the farmer can convert an investment to cash when needed Coomes et al (2008) and Holmes et al (2017) 6 Investment costs a…”
Section: Economic Stabilitymentioning
confidence: 99%
“…Next, Holmes et al [29] also find that success of REDD+ requires more nuance and alignment with local needs. The authors used semi-structured interviews and participatory methods over the span of 11 years in an Embera community in Panama to examine how local communities sought to reduce emissions from deforestation and benefit from carbon offset trading while improving local livelihoods.…”
Section: Lessons From Redd+ Early Actionsmentioning
confidence: 99%